2006
DOI: 10.1021/jp0638484
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Pyridine-Catalyzed SiO2 Atomic Layer Deposition Studied by Fourier Transform Infrared Spectroscopy

Abstract: Fourier transform infrared (FTIR) investigations were performed to study the mechanism of catalytic SiO 2 atomic layer deposition (ALD) using pyridine as the catalyst. Pyridine adsorption on hydroxylated SiO 2 surface was examined by monitoring both the changes to the O-H stretching vibrations and the appearance of pyridine molecular vibrations. The strong hydrogen bonding of pyridine to the isolated hydroxyl groups with a desorption energy of 9 ( 2 kcal/mol is believed to make oxygen a stronger nucleophile fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 42 publications
2
68
0
1
Order By: Relevance
“…The interaction was stronger in GG as compared to the WG. Another possible interaction may be among the protein amines and the polar groups of span-40 [47] .…”
Section: Molecular Characterization Studiesmentioning
confidence: 99%
“…The interaction was stronger in GG as compared to the WG. Another possible interaction may be among the protein amines and the polar groups of span-40 [47] .…”
Section: Molecular Characterization Studiesmentioning
confidence: 99%
“…Both were tested at partial pressures of 0.2 Torr. 17 Ammonia was tested at the same vapor pressure as the other two catalysts, as well as at 1.6 Torr. Loading of MP groups calculated by TGA indicated that when using pulses of equivalent length, piperidine gives higher loading than ammonia and pyridine.…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss observed in first decomposition step was about 5%. The next decomposition occurred at 300-400 1C, due to the removal of pyridine [24]. The weight loss for this step was about 20%.…”
Section: Thermal Analysismentioning
confidence: 99%